Ressonância Ferromagnética em Super-Redes NiFe/Ru - LANDI JUNIOR, Salmon (2009)
The Ferromagnetic Resonance (FMR) technique was used to study the magnetic anisotropy of NiFe/Ru multilayers. The FMR spectra and absorption fields of multilayers with Ru layers thickness bellow 20 Å are the same as that of single monolayer films. Evidence of the coupling between the magnetic layers also is given by the fact that for the sample with Ru thickness equal to 7 Å, in normal configuration of the applied static field, spin-wave resonance modes also are excited by the microwave field. The interlayer coupling constant obtained is equal to 1, 1 £ 10¡7 erg/cm. For the set of samples with different NiFe thicknees, the analysis of the effective magnetic anisotropy in terms of volume and surface contributions, gives KV = 3, 4 £ 106 erg/cm3 and KS = 1, 2 erg/cm2.